1996
DOI: 10.1111/j.1835-9310.1996.tb00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Homo Nullius or `Where Have All the People Gone‘? Refiguring Marine Management and Conservation Approaches

Abstract: In Australia, much has been said and written about recent events which finally brought about the rejection of the Western legal concept of terra nullius. The legal recognition of native title in Australia and elsewhere, does not necessarily signify a corresponding and dramatic change in the social status and political position of indigenous peoples. This discontinuity between legal and social discourses is particularly evident when it comes to matters concerning conservation, resource management and sustainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Customary marine resource management practices in the Indo-Pacific are often focused on social goals such as minimizing conflict among coastal communities, rather than western ideals of conservation or fisheries management (Polunin, 1984;Pannell, 1996;Aswani et al, 2007). Although the primary aim of the Panglima Laot is to minimise conflict among fishers, our findings indicate that controls on fishing gears indirectly yield conservation benefits including, healthier coral reefs that support a greater biomass of reef fish, including important trophic groups, such as herbivores that are essential for promoting reef resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Customary marine resource management practices in the Indo-Pacific are often focused on social goals such as minimizing conflict among coastal communities, rather than western ideals of conservation or fisheries management (Polunin, 1984;Pannell, 1996;Aswani et al, 2007). Although the primary aim of the Panglima Laot is to minimise conflict among fishers, our findings indicate that controls on fishing gears indirectly yield conservation benefits including, healthier coral reefs that support a greater biomass of reef fish, including important trophic groups, such as herbivores that are essential for promoting reef resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Customary management systems are frequently motivated by utilitarian social and economic goals, rather than any conservation ethic (Polunin, 1984;Pannell, 1996;Cinner & Aswani, 2007). The ability of customary systems to meet community needs such as providing fish for harvest, reducing conflict among resources users and improving yields can lead to higher levels of compliance, and ultimately better ecological outcomes than externally imposed biodiversity conservation (McClanahan et al, 2006a;Cinner & Aswani, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…6 The activities of villagers within the Park are now restricted to miniscule areas of land and sea designated as part of the 'traditional use zone'. Technology permitted in this zone is restricted to 'traditional tools', while the use of these tools is 'licensed by the Head of Komodo National Park' (Pannell 1996) In this respect, the Plan reflects an earlier ecological assessment, which concluded that 'limited ecotourism and research' are the 'only true sustainable uses' of the terrestrial portions of the Park.…”
Section: Culture Wars IImentioning
confidence: 99%
“…Reflecting The Nature Conservancy's preservationist view of nature as either valorised pristine areas or demonised expendable environments, the current plan thus separates the population of the Park into a near (if not already) extinct Indigenous minority and an endangering immigrant majority (see Pannell 1996).…”
Section: Culture Wars IImentioning
confidence: 99%
“…In fact, the fishers for whom Nietschmann advocates have never been on the map, they are Homo nullius. This is not limited to this particular case, as it is common in many marine management decisions (Pannell, 1996). Human territories in the ocean, while a spatial practice, have been rendered invisible through the mapping of the sea as a blue field (Steinberg, 2001).…”
Section: Marine Protected Areas: Territorializing Objects and Subjectmentioning
confidence: 99%